Pediatric acute lymphoblastic leukemia with t(1;19)/TCF3‐PBX1 in Taiwan. Issue 10 (24th April 2017) - Yen, Hsiu‐Ju; Chen, Shih‐Hsiang; Chang, Tsung‐Yen; Yang, Chao‐Ping; Lin, Dong‐Tsamn; Hung, Iou‐Jih; Lin, Kai‐Hsin; Chen, Jiann‐Shiuh; Hsiao, Chih‐Cheng; Chang, Tai‐Tsung; Chang, Te‐Kao; Peng, Ching‐Tien; et al.
Abstract: Background: In childhood acute lymphoblastic leukemia (ALL), t(1;19)(q23;p13.3) with TCF3‐PBX1 fusion is one of the most frequent translocations. Historically, it has been associated with poor prognosis. Intensive treatment, however, has improved its outcome. We determined the outcome of children with this genotype treated with contemporary intensive chemotherapy in Taiwan. Procedure: In Taiwan Pediatric Oncology Group 2002 ALL studies, genotypes were determined by cytogenetic analysis and/or reverse transcriptase polymerase chain reaction assay. Based on presenting features, immunophenotype and genotype, patients were assigned to one of the three risk groups: standard risk (SR), high risk (HR), or very high risk (VHR). The patients with t(1;19)/ TCF3‐PBX1 were treated in the HR arm receiving more intensive chemotherapy. The outcomes of patients with t(1;19)/ TCF3‐PBX1 were compared to that of patients with other subtypes of B‐precursor ALL (B‐ALL). Results: Of the 1, 129 patients with B‐ALL, 64 (5.7%) had t(1;19)/ TCF3‐PBX1 ; 51 of whom were treated in the HR arm, but 11 were treated in the VHR and 2 in the SR arm because of physician's preference. As a group, 64 patients with t(1;19)/ TCF3‐PBX1 had similar 5‐year event‐free survival (83.3 ± 4.8%) as those with TEL‐AML1 (85.2 ± 3.4%, P = 0.984) or those with hyperdiploidy >50 (84.0 ± 3.1%, P = 0.748). The cumulative risk of any (isolated plus combined) central nervous system relapse among patients with t(1;19)/ TCF3‐PBX1 (8.7 ± 3.8%) tended to be higher than that of patients with TEL‐AML1 (5.8 ± 2.3%, P = 0.749) or those with hyperdiploidy (4.1 ± 1.8%, P = 0.135), albeit the differences did not reach statistical significance. Conclusions: With contemporary intensive chemotherapy, children with t(1;19)/ TCF3‐PBX1 fared as well as those with favorable genotypes ( TEL‐AML1 or hyperdiploidy).